Innovations induce asymmetric employment movements - Thomas Zwick (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
This paper provides a labour supply explanation to the observation that in Germany employment changes are asymmetric during the business cycle. Employment increases are slower, because the reservation wage of workers increases in times of job uncertainty. Workers are afraid in those periods of losing their sunk and necessary human capital investments. They weigh the risks and benefits of investing in human capital with their certain outside option when they decide about staying in the labour market. Human capital investments are sunk and necessary, because firms need new skills while older skills get obsolete at a constant rate. Skill obsolescence is induced by innovations.
Keywords: O30; J22; J24; 330; Arbeitsmarkttheorie; Anspruchslohn; Innovation; Technischer Fortschritt; Bildungsinvestition; Sunk Costs; Konjunktur; Beschäftigungseffekt; Theorie; Deutschland